Treatment with LPS plus INF-γ induces the expression and function of muscarinic acetylcholine receptors, modulating NIH3T3 cell proliferation: participation of NOS and COX - Español, Alejandro Javier (2014)
BACKGROUND AND PURPOSE: LPS and IFN-γ are potent stimuli of inflammation, a process in which fibroblasts are frequently involved. We analysed the effect of treatment with LPS plus IFN-γ on the expression and function of muscarinic acetylcholine receptors in NIH3T3 fibroblasts with regards to proliferation of these cells. We also investigated the participation of NOS and COX, and the role of NF-κB in this process. EXPERIMENTAL APPROACH: NIH3T3 cells were treated with LPS (10 ng·mL(-1)) plus IFN-γ (0.5 ng·mL(-1)) for 72 h (iNIH3T3 cells). Cell proliferation was evaluated with MTT and protein expression by Western blot analysis. NOS and COX activities were measured by the Griess method and radioimmunoassay respectively. KEY RESULTS: The cholinoceptor agonist carbachol was more effective at stimulating proliferation in iNIH3T3 than in NIH3T3 cells, probably due to the de novo induction of M3 and M5 muscarinic receptors independently of NF-κB activation. iNIH3T3 cells produced higher amounts of NO and PGE2 than NIH3T3 cells, concomitantly with an up-regulation of NOS1 and COX-2, and with the de novo induction of NOS2/3 in inflamed cells. We also found a positive feedback between NOS and COX that could potentiate inflammation. CONCLUSIONS AND IMPLICATIONS: Inflammation induced the expression of muscarinic receptors and, therefore,stimulated carbachol-induced proliferation of fibroblasts. Inflammation also up-regulated the expression of NOS and COX-2, thus potentiating the effect of carbachol on NO and PGE2 production. A positive crosstalk between NOS and COX triggered by carbachol in inflamed cells points to muscarinic receptors as potential therapeutic targets in inflammation.